Chemical Investigation of Some Medicinal Plants of Shiwalik Hills - Tyagi, S.; Sarraf, S.; Ojha, A.C.; Rawat, G.S. (Asian Journal of Chemistry, 2010)
Sugars and vitamins were estimated in four medicinal plants viz., Ageratum conyzoides, Colebrookea oppositijalia, Fumaria parviflora. and Pogostemon plectranthoides. More free sugars are present in C. oppositifolia. Pogosteman leaves are rich in reducing sugars. Total sugar is in excess in the F. parviflora. Vitamin A is present in the flowers of A. Conyzoides and in the leaves of F. parviflora. Vitamin B is present in A. conyzoides. F. parviflora and P. plectranthoides and absent in C. oppositifolia.